2020
DOI: 10.1002/lary.28968
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Continuous Positive Airway Pressure After Sinonasal Surgery

Abstract: Objectives/Hypothesis For patients with obstructive sleep apnea (OSA) undergoing sinonasal surgery, there is a lack of consensus on the risk and appropriate postoperative use of continuous positive airway pressure (CPAP). The aim of this study was to assess the tolerability of restarting CPAP on postoperative day one. Study Design Prospective cohort study. Methods A prospective study on patients with OSA on CPAP who required a septoplasty/turbinectomy and/or functional endoscopic sinus surgery (FESS) was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…After screening for relevance, 19 studies that investigated PAP therapy data, such as optimal pressure levels and/or usage time before and after surgery, were retrieved for further review [ 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. We excluded eight studies evaluating the effect of nasal surgery alone on PAP therapy [ 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Two other studies were excluded due to the lack of data required for meta-analysis [ 15 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening for relevance, 19 studies that investigated PAP therapy data, such as optimal pressure levels and/or usage time before and after surgery, were retrieved for further review [ 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. We excluded eight studies evaluating the effect of nasal surgery alone on PAP therapy [ 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Two other studies were excluded due to the lack of data required for meta-analysis [ 15 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some clinical studies have reported that surgical management influenced PAP therapy such as optimal levels and the duration of use [ 14 , 15 ]. Two recent meta-analyses demonstrated that surgical modifications of the upper airway were associated with decreases in optimal PAP levels and improvement in PAP adherence [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 Management of nasal obstruction (humidification, nasal decongestants, steroids, and nasal surgery), while not significantly improving OSA severity, has the potential to improve PAP compliance in terms of duration of use at night and daily usage rate. [29][30][31][32][33] In this study, a separate analysis of patients with rhinopathy suggested that nasal treatment was associated with PAP compliance. Further studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…These included severity of a patient's OSA, type of CPAP mask used, and surgical maneuvers performed (most notably tip work and osteotomies) 42 . A small study by Reilly et al demonstrated safety of restarting CPAP within 24 hours after septoplasty 43 . The decision to restart CPAP therapy should be individualized to the patient.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…42 A small study by Reilly et al demonstrated safety of restarting CPAP within 24 hours after septoplasty. 43 The decision to restart CPAP therapy should be individualized to the patient. Factors to consider include severity of OSA, other comorbidities, and surgical maneuvers performed.…”
Section: Resuming Continuous Positive Airway Pressure Therapymentioning
confidence: 99%